CAR-NK Cells: From Natural Basis to Design for Kill - Khawar, Muhammad Babar; Sun, Haibo (Frontiers in Immunology, 2021)
The chimeric antigen receptor (CAR) is a fusion protein with an extracellular antigen recognition domain and numerous intracellular signaling domains that have been genetically modified. CAR-engineered lymphocyte-based therapies have shown greater success against tumors. CAR-T therapy has been found highly effective against blood cancers, but potential fatal toxicities like cytokine release syndrome and high costs are the potential shortcomings that limit their clinical applications and remain to overcome. Natural killer (NK) cells are the focal point of present immunological research due to their receptors that prove to be promising for immunotherapy against cancer. However, the success of manipulating NK cells against malignancies is modest to date. Recent achievements in the understanding of the NK cell receptors have greatly transformed our understanding of the ability of NK cells in recognizing and killing tumor and infected cells. Because of their unique recognition mechanisms, powerful cytotoxic effects specifically to cancer cells in both CAR-dependent and CAR-independent manners, and clinical safety, CAR-NK cells may serve as an alternate candidate for cancer retargeting. Moreover, they can serve as an “off-the-shelf product” as NK cells from allogeneic sources can also be utilized in immunotherapies as they show a reduced risk of alloreactivity. Although the fundamental research is still in its infancy, this review provides an overview of recent developments carried out to design CAR constructs to stimulate NK activation, manipulate NK receptors for improving the efficiency of immunotherapy against cancer, summarizes preclinical and clinical updates of CAR-NK cells against both hematological malignancies and solid tumors, and confronts current challenges and obstacles of their applications. Last but not least, this review will provide insight into prospective novel approaches to further enhance the efficiency of CAR-NK therapies and highlight the potential questions that need to be addressed in the future.